Effect of Javascript on middle schoolers' attitute toward computer course - Ibrahim Bastug; Kagan Kircaburun (Journal of Pedagogical Research, 2017)
In recent years, the number of students who have chosen computer science related undergraduate departments has decreased rapidly. Moreover, students who prefer computer science and programming departments appear to be unsuccessful in programming classes due to the complexity and frustrating difficulties of programming learning. One of the solutions to overcome this problem is to make the students adapt and warm up to the programming issues from the lower grades. In order students, who are in the age of development at primary and junior high school level, to love and learn programming, various enjoyable methods are applied. Scratch software is one way of teaching programming to secondary school students. This study investigated how the attitudes of 5th and 6th grade students towards information technology course changed after Scratch software and programming language and Javascript programming language were used. A 2x2x2 factorial experimental design was used in the study. According to the analysis, it was found that both methods are effective on the students' attitudes. But there was no significant difference between them.